Revisiting lignin: a tour through its structural features, characterization methods and applications. Issue 16 (16th April 2021) - Melro, Elodie; Filipe, Alexandra; Sousa, Dora; Medronho, Bruno; Romano, Anabela
Abstract : A pedagogical overview of the main extraction procedures and structural features, characterization methods and state-of-the-art applications. Abstract : Lignin is a complex organic polymer found in the plant cell wall with important biological functions, such as water transport, mechanical support, and resistance to various stresses. It is considered the second most abundant biopolymer on earth and the largest natural source of aromatics. Despite being annually co-produced in massive amounts, during cellulose fragmentation in the pulp industry and ethanol biorefinery, it is clearly undervalued; most of it is discarded or burned as fuel for energy production and, so far, only ca. 1–2% of lignin has been utilized as a high-value product. This underuse makes lignin the future resource of choice to produce green fuels and a wide range of added-value biomaterials and chemicals, which can contribute to the transition to more sustainable industries. However, its great variability between plant families combined with its complex and chemically inert structure is challenging researchers who seek for strategies regarding its valorization. With this scope, several different approaches have emerged regarding the development of better and efficient isolation methods, purification and characterization techniques, and improved methodologies for lignin chemical modification and blending with other compounds. These improvements represent important opportunities for the creation of value-added lignin-based biopolymers and materials and some have already shown potential to be scaled up. All these aspects are pedagogically introduced and discussed in this review.